2010
DOI: 10.1074/jbc.m109.061747
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Fluxes during Strong Carbon Catabolite Repression by Malate in Bacillus subtilis

Abstract: Commonly glucose is considered to be the only preferred substrate in Bacillus subtilis whose presence represses utilization of other alternative substrates. Because recent data indicate that malate might be an exception, we quantify here the carbon source utilization hierarchy. Based on physiology and transcriptional data during co-utilization experiments with eight carbon substrates, we demonstrate that malate is a second preferred carbon source for B. subtilis, which is rapidly co-utilized with glucose and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
110
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(122 citation statements)
references
References 58 publications
12
110
0
Order By: Relevance
“…A recent work shows that B. subtilis prefers MA as a carbon source and inflicts metabolite repression to take up other carbon sources for an efficient MA uptake (for review, see Fernie and Martinoia, 2009;Kleijn et al, 2010). This recent data validates the specificity and preference of B. subtilis for MA.…”
Section: Foliar Mamps Trigger Root Fb17 Colonizationsupporting
confidence: 50%
“…A recent work shows that B. subtilis prefers MA as a carbon source and inflicts metabolite repression to take up other carbon sources for an efficient MA uptake (for review, see Fernie and Martinoia, 2009;Kleijn et al, 2010). This recent data validates the specificity and preference of B. subtilis for MA.…”
Section: Foliar Mamps Trigger Root Fb17 Colonizationsupporting
confidence: 50%
“…Recently, it was shown that in Bacillus subtilis Lmalate is coutilized with glucose and that it is a second preferred carbon source (5,14,27), and it would be interesting to test whether C 4 -dicarboxylates are also preferred carbon sources in E. coli.…”
Section: Resultsmentioning
confidence: 99%
“…46 Glucose is the preferred substrate in B. subtilis, and its presence represses the utilization of other alternative substrates. On the basis of physiological and transcriptional data from coutilization experiments with eight different carbon substrates, Kleijn et al 47 demonstrated that malate is a second preferred carbon source for B. subtilis, which is rapidly coutilized with glucose and strongly represses the uptake of alternative substrates.…”
Section: Bacillalesmentioning
confidence: 99%